2020
DOI: 10.1021/acsbiomaterials.9b01911
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Biological Activity of 3D-Printed Polycaprolactone/Magnesium Porous Scaffolds for Critical Size Bone Defect Repair

Abstract: Polycaprolactone (PCL) is widely used in bone tissue engineering due to its biocompatibility and mechanical strength. However, PCL is not biologically active and shows poor hydrophilicity, making it difficult for new bones to bind tightly to its surface. Magnesium (Mg), an important component of natural bone, exhibits good osteo-inductivity and biological activity. Therefore, porous PCL/Mg scaffolds, including pure PCL, PCL/5%Mg, PCL/10%Mg, and PCL/15%Mg, were prepared to elucidate whether the porous structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
(64 reference statements)
1
25
0
Order By: Relevance
“…Results demonstrated that Mg–PCL scaffold could promote bone growth and might be an ideal candidate for bone tissue engineering; however, it can’t inhibit tumor metastasis. This result is partly consistent with the study of Zhao et al, which demonstrated PCL/10% Mg composite scaffolds could promote bone defect repair at an early stage with good cytocompatibility [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Results demonstrated that Mg–PCL scaffold could promote bone growth and might be an ideal candidate for bone tissue engineering; however, it can’t inhibit tumor metastasis. This result is partly consistent with the study of Zhao et al, which demonstrated PCL/10% Mg composite scaffolds could promote bone defect repair at an early stage with good cytocompatibility [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the rods prepared by extrusion were cut to obtain the wafers used in the experiment, which consequently caused uneven structures of the disc surface, as observed from the SEM images. Many studies have demonstrated that a rough structure is advantageous for cell adhesion and proliferation [ [24] , [25] , [26] ]. The SEM scanning results demonstrated that the TiCu/TiCuN coating was distributed in a granular form on the surface of the CFR-PEEK substrate, uniformly covering the PEEK matrix and the carbon fibre part.…”
Section: Discussionmentioning
confidence: 99%
“…77,5 Zhao et al fabricated the PCL/magnesium porous scaffold and demonstrated that when the weight masses of magnesium particles were 5 and 10 wt %, the attachment of BMSCs' increased through enhanced surface hydrophilicity. 85 Yin et al found that the fraction of initial cell adhesion in hydrogels containing 100 mM Mg ions was 15.69%, which was much higher as compared to the control group (3.50 ± 1.40%). 86 It is proposed that magnesium adjusts the direction of fibronectin and enhances its receptors' affinity, resulting in increased integrin binding that promotes cellular adhesion.…”
Section: Effects Of Magnesium Ions On Bone Tissue Engineeringmentioning
confidence: 97%